Mists of regret : culture and sensibility in classic French film - Andrew, Dudley, 1945- (Princeton University Press, 1995)
An examination of pre-World War II French cinema, which analyzes the works of such directors as Renoir, Gremillon and Chenal in order to explain why the French were first to give maturity to the sound film. The study also describes the importance of these films in the context of French culture.